Generation and Intensification of Mesoscale Anticyclones by Orographic Wind Jets: The Case of Ierapetra Eddies Forced by the Etesians. Issue 8 (31st July 2020) - Ioannou, Artemis; Stegner, Alexandre; Dubos, Thomas; Le Vu, Briac; Speich, Sabrina
Abstract: Motivated by the recurrent formation and intensification of the Ierapetra anticyclones in the southeast of Crete, we investigated with a reduced gravity model the response of the oceanic surface layer to a seasonal wind jet that varies slowly (over several weeks or months) and mimics the Etesian winds. Our study answers why the oceanic response to such forcing is mainly a large and intense anticyclone. We build a dimensionless parameter that integrates in time the Ekman pumping and quantifies the relative amplitude of the isopycnal displacement induced by the local wind stress curl. According to the range of the wind forcing parameter, the oceanic response to a symmetric wind jet could be a symmetric dipole or a strongly asymmetric structure dominated by an intense and robust anticyclone. This intrinsic asymmetry is driven by the finite isopycnal displacements that occur when the wind forcing parameter reaches unity. Since the anticyclonic wind shear for the Etesian wind jet is 2 times larger than the cyclonic one, the asymmetry of the oceanic response is enhanced. Several weeks after the wind forcing has stopped, an intense mesoscale anticyclone which satisfies the cyclogeostrophic balance remains. Moreover, if a similar wind jet blows on a preexisting anticyclone, the latter remains robust and coherent and gets reintensified in agreement with the previous analysis of remote sensing observations. Hence, this paper is the first numerical study which provides a dynamical understanding for the formation of the single Ierapetra anticyclones and explains their intensification 1 year after formation. Key Points: Orographic wind jets are a driving mechanism for generation and intensification of mesoscale anticyclones The oceanic response to a transient symmetric wind forcing could be strongly asymmetric A numerical study that provides a dynamical understanding for the wind‐forced mesoscale Ierapetra anticyclones